Kemampuan Representasi Siswa Kelas IX dalam Menyelesaikan Soal Pola Bilangan - Putri Dwi Arianti; Indhira Febrianti Aqilla; Nur Rahma Haliza; Ulfia Churidatul Andriani (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2026)
This study investigates ninth-grade students’ mathematical representation abilities in solving number pattern problems, focusing on how they construct and apply visual, symbolic, and verbal forms of representation. Using a descriptive qualitative design, research subjects were selected purposively based on diagnostic test results. Data from written tests were analyzed inductively following the Miles and Huberman model. The findings indicate that students who used structured visual representations, such as paired number lists, were more successful in identifying pattern regularities and reduced cognitive load. However, symbolic representations were less consistent. Although some students were able to recall and apply the arithmetic sequence formula, errors occurred during substitution and algebraic manipulation, indicating partial conceptual understanding. Verbal explanations also emerged but were insufficient to bridge visual and symbolic reasoning. Overall, this study emphasizes the importance of learning strategies that support the integration of visual, verbal, and symbolic representations in solving number pattern problems. Therefore, teachers are advised to provide contextual problems and discussion activities that can train students to use various forms of mathematical representation in an integrated manner.